Modalitas Yusran Amirullah dalam Pemilihan Kepala Daerah Kabupaten Lampung Timur tahun 2020 - Salbari, Al Rizky; Juantara, Bendi; Kurniwan, Robi Cahyadi (Penerbit Goodwood, 2022)
Purpose: to determine the effect of economic capital on political capital and social capital. Method: This study uses a descriptive research method with a qualitative approach and the theory used is political modality. According to Ratnia Sholihah, the modalities in political contestation are divided into three, namely political capital, economic capital and social capital. Result: This study indicate that economic capital is very influential on the other 2 capitals. It can be seen from the number of political parties in a coalition and the low number of votes which makes political capital and social capital to follow along with the maximum economic capital. Limitation: Therefore, the formulation adopted by the author in this study is